1991
DOI: 10.1002/eji.1830210726
|View full text |Cite
|
Sign up to set email alerts
|

The function of human NK cells is enhanced by β‐glucan, a ligand of CR3 (CD11b/CD18)

Abstract: Cells responsible for the natural killer (NK) effect in the human blood can be collected in the low-density lymphocyte subset and the majority of them express CR3. In addition to the iC3b binding site the CR3 molecules possess an epitope which binds beta-glucan. Ligands of this site can deliver activation signals to CR3-carrying monocytes and neutrophils. We found that the function of NK cells was also potentiated by preincubation with beta-glucan. The treatment increased the proportion of target-binding lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 27 publications
(8 reference statements)
2
51
0
Order By: Relevance
“…M522 is the only MoAb to CR3 that has been reported to stimulate a neutrophil respiratory burst [30], Taken together, these results suggest that M522 binds at or near to the same sile in CR3 as does //-glucan. Our own recent experiments have confirmed the linding of Di Renzo et al [29] and in addition have shown that the /J-glucanenhanced killing of K562 cells is blocked by staurosporine, genistein. or herbimycin A, These kinase inhibitors blocked only the enhancement of cytotoxicity stimulated by /i-glucan, and not the basal levels of CR3-independent cytotoxicity.…”
Section: Activation Of Nk Cell Cr3 Hy Soluble Ft-glucansupporting
confidence: 84%
See 1 more Smart Citation
“…M522 is the only MoAb to CR3 that has been reported to stimulate a neutrophil respiratory burst [30], Taken together, these results suggest that M522 binds at or near to the same sile in CR3 as does //-glucan. Our own recent experiments have confirmed the linding of Di Renzo et al [29] and in addition have shown that the /J-glucanenhanced killing of K562 cells is blocked by staurosporine, genistein. or herbimycin A, These kinase inhibitors blocked only the enhancement of cytotoxicity stimulated by /i-glucan, and not the basal levels of CR3-independent cytotoxicity.…”
Section: Activation Of Nk Cell Cr3 Hy Soluble Ft-glucansupporting
confidence: 84%
“…In addition. NK cells were shown to be similarly activated by F(ab'); fragments ofthe anti-CR3 MoAb M522 [29]. M522 is the only MoAb to CR3 that has been reported to stimulate a neutrophil respiratory burst [30], Taken together, these results suggest that M522 binds at or near to the same sile in CR3 as does //-glucan.…”
Section: Activation Of Nk Cell Cr3 Hy Soluble Ft-glucanmentioning
confidence: 98%
“…It has been shown that b-glucans modulate NK cell function through a receptor distinct from CR3 [21,33]. However, we did not detect the bGR on these cells (CD56 + CD16 + ) (Fig.…”
Section: Distribution Of the Bgr In Human Peripheral Blood Cellsmentioning
confidence: 61%
“…The activity of bGR has been described on a variety of human leukocytes including monocytes [17], macrophages [18], eosinophils [19], neutrophils [20] and NK cells [21], and we had previously detected bGR mRNA in some of these cell populations [10]. To demonstrate the presence of this receptor on these cells, we examined surface expression of bGR on human PBL by flow cytometry, using GE2 to detect both major functional bGR isoforms.…”
Section: Distribution Of the Bgr In Human Peripheral Blood Cellsmentioning
confidence: 99%
“…Not only did anti-CR3 fail to inhibit NK cell killing of K562 cells [27], but aiso NKcell attachment to target cells coated with fixed iC3b did not stimulate cytotoxicity [4.28]. Recognizing the potential of jiglucan to activate neutrophil CR3, Di Renzo a ai [29] showed that soluble /f-glucan would greatly enhance NK cell-mediated cytotoxicity of K562 cells, and that this enhanced cytotoxicity was blocked by the anti-CR3 MoAb OKMl. In addition.…”
Section: Activation Of Nk Cell Cr3 Hy Soluble Ft-glucanmentioning
confidence: 99%